INCLUSIVE EDUCATION AT SECONDARY LEVEL IN ISLAMABAD: PROSPECTS AND CHALLENGES - Tayyaba Waseem; Farheen Amjad; Farah Abdul Qadir (JIE, 2025)
This Mixed-method study aimed to examine the prospects and challenges of inclusive education at secondary level schools. The major objectives were to examine the current status of inclusive education at secondary level and to investigate various prospects, challenges, and possible solutions for the successful implementation of inclusive education. The sample of the study constituted 19 principals, selected through universal sampling method, and 210 teachers through random sampling technique. For data collection, a questionnaire was used for teachers while principals were interviewed. Quantitative data were analyzed through descriptive statistics while qualitative data were analyzed through thematic analysis. The study revealed that teachers view inclusive education positively, seeing it as beneficial for students' academic, social, and personal development while promoting equality and diversity. However, inadequate infrastructure and insufficient availability of essential tools such as ramps, braille, hearing aids elevators, accessible washrooms, etc. limit access for physically disabled students. Principals emphasized the need for teacher training and an inclusive curriculum to support implementation. Although some schools have adopted inclusive practices, most face challenges due to limited resources and infrastructure. Addressing these needs with appropriate funding and training is essential for successful inclusive education. Keywords: Inclusive education, secondary level, Islamabad, prospects, challenge